AB0340 Tapering Strategy in Patients with Rheumatoid Arthritis Receiving Tocilizumab. (15th July 2016) - Tornero, C.; Plasencia, C.; Pascual, D.; Jurado, T.; Monjo, I.; Paredes, M.B.; Moral, E.; Pieren, A.; Nuño, L.; Bonilla, G.; Peitedo, D.; Mola, E.M.; et al.
Abstract : Background: Clinical trials have demonstrated the efficacy of Tocilizumab (TCZ) for patients with rheumatoid arthritis (RA). Several studies have demonstrated that dose tapering of TNF-inhibitors is a feasible therapeutic option in rheumatic patients with low disease activity (LDA). Nevertheless, few reports analyse the effectiveness of dose-tapering of TCZ. Objectives: To evaluate the clinical outcome and incidence of flares in patients with RA in remission or LDA under a tapering strategy with TCZ and to analyse the influence of the tapering on serum drug levels. Methods: Of a cohort of 34 adult patients with RA under therapy with TCZ, 13 patients with sustained LDA or remission (DAS 28-ESR <3, 2) under a tapering strategy were included. Clinical disease activity (DAS-28-ESR, CDAI and SDAI), serological data (C-reactive protein, erythrocyte sedimentation rate) and serum TCZ levels were evaluated at the visit prior to starting tapering strategy (V0) and at the last visit available during a three-year follow-up period (LV). The tapering strategy consisted in a progressive interval prolongation and/or dose reduction. A flare was defined as an increase of the DAS28 greater than 3.2 plus a delta-DAS28 (related to pre-tapering DAS28) lower than -0.6. The number of flares, time to first flare and the activity in the worst flare were collected. In the case of a flare, the concomitant therapy and TCZ dose could be intensified. Blood samples were collected just before the infusion and serum drug levels were measured by ELISA. Results: The baseline demographic and clinical characteristics are shown in Table 1 . No differences in the clinical activity (DAS28: 2, 28± 0, 8 at V0 vs 2, 5±0, 7 at LV, p=0, 25; CDAI 4, 71: ±5, 1 at V0 vs 5, 71±5, 1 at LV p=0, 08; SDAI (4, 99±5, 3 at V0 vs 5, 0 ±4, 8 at LV, p=0, 052), number of swollen joints (1, 69±3, 2 at V0 vs 1, 46±1, 8 at LV; p=0, 091) and tender joints (0, 69± 1, 1 at V0 vs 0, 62±0, 96 at LV; p=0, 243) and acute-phase reactants (CRP: 0, 48±0, 6 at V0 vs 0, 54±0, 6 at LV, p=0, 219; ESR: 7, 69±3, 1 at V0 vs 10, 3±5, 4 at LV, p=0, 152) between V0 and LV were observed. The decrease of drug levels between V0 and LV was not significant (15, 4±9, 31 vs 3, 02±5, 99, p=0, 867). During the follow-up period, 6 (43%) patients presented flares. The number of flares after the tapering strategy was 1, 2±1, 6 and the time to the first flare was 1±0, 4 years. The following clinical and disease activity data and serum TCZ levels were registered at the worst flare: STJ: 6, 7± 7, 4 and TJC: 1, 83±1, 2; DAS28: 3, 99±0, 6, CDAI: 14, 7± 8, 2 and SDAI: 14, 5±9, 08; TCZ levels: 0, 86±1, 78. Most patients after having a flare (4/6) reached remission or LDA at the end of the study, and no significant differences in LDA were observed between those with or without flares (DAS-28 LV<3, 2:4/11 (36, 4%) vs 7/11 (63, 6%), p=0, 097; CDAI LV <10: 4/10 (66, 7%) vs 6/10 (85, 7%), p=0, 42; SDAI LV <11: 4/11 (36, 4%) vs 7/11 (63, 6%), p=0, 097, respectively). All of the patients continued on tapering strategy and no patients dropped out because of inefficacy. Conclusions: The tapering strategy in patients with RA with LDA or remission receiving TCZ appears to be feasible, resulting in a low proportion of patients with flares and a good longterm clinical disease activity control. Disclosure of Interest: C. Tornero Grant/research support from: Funded by an unrestricted medical grant from Pfizer., C. Plasencia: None declared, D. Pascual: None declared, T. Jurado: None declared, I. Monjo: None declared, M. B. Paredes: None declared, E. Moral: None declared, A. Pieren: None declared, L. Nuño: None declared, G. Bonilla: None declared, D. Peitedo: None declared, E. M.Mola: None declared, A. Balsa: None declared